Assessment of contrast perception of obstacles in tunnel entrance - Ahmad Mehri; Somayeh Farhang Dehghan; Milad Abbasi; Mohammad Hosein Beheshti; Javad Sajedifar; Sayed Mohammad Jafari; Monireh Khadem; Roohalah Hajizadeh (Tabriz University of Medical Sciences, 2018)
Background: The purpose of this study was to assess the contrast perception of obstacles in a tunnel entrance which was placed in Ilam Province, Iran.Methods: An obstacle with the reflection coefficient of 20% was mounted at the entrance of thetunnel and then, the car was placed near the tunnel entrance and the intrinsic luminance of the road (Lr,intrinsic) and obstacle (Lo,intrinsic) were measured inside the car using the luminance meter.Results: Intrinsic luminance of obstacle and road at the entrance of the tunnel were measured as 41 and 17 cd/m2, respectively. The contrast perception of obstacle in deriver's eyes and in the safe stopping distance (SSD) from the tunnel entrance was determined as 2.79 cd/m2. At the entrance of the studied tunnel, the contrast perception of obstacles with the reflection coefficient of 20% was lower than the minimum contrast perception (28%) recommended by International Commission on Illumination.Conclusion: The main conclusion that can be drawn from it, is that this obstacle in the SSD from the tunnel entrance cannot be conceived by the drivers, which may lead to higher rate of road traffic crashes.